DOP76 No durable impact of COVID-19 on disease activity and microbiome composition in patients with IBD. (27th May 2021) - Funez-dePagnier, G; Lima, S; Duenas-Bianchi, L; Lai, D; Ahmed, W; Battat, R; Scherl, E; Lukin, D; Longman, R
Abstract: Background: Although patients with inflammatory bowel disease (IBD) reported an increased frequency of gastrointestinal (GI) symptoms following infection, the durable impact of COVID-19 on underlying IBD is not well defined. Methods: In 118 IBD patients with COVID-19, clinical and endoscopic IBD activity, laboratory markers (ESR, CRP, hemoglobin (Hb), fecal calprotectin(FCP)), and medication utilization was assessed up to 6 months post-infection and compared to during infection or up to 6 months prior to infection. Active disease was defined by a Harvey Bradshaw Index > 4, Mayo Score ≥2, SES-CD ≥2, Mayo endoscopic score ≥1. 16S rRNA analysis was used to evaluate microbiome composition in a subset of 12 patients before and after COVID-19. Results: Although upper respiratory (86.6%) and new GI symptoms (39.1%) were common in patients with IBD, there was no significant change in IBD clinical disease activity (Pre vs. Post-COVID-19 HBI: 4.7 vs. 4.9; partial Mayo: 3.0 vs. 2.1), endoscopic evaluation (Pre vs. Post-COVID-19 SES-CD: 7.2 vs. 8.9, Mayo endoscopic score: 1.5 vs. 1.7), or laboratory markers (Pre vs. Post-COVID-19 CRP: 1.2 vs. 1.3; ESR: 25 vs. 26; Hb 12.8 vs. 13.2; FCP: 388 vs. 250) up to 7 months post-COVID-19 compared to the 6 months prior to infection (Table 1). Overall active disease was present in 60% of the cohort prior to COVID-19 and 55% and 59% during and post-COVID-19, respectively. More subjects (8.5%) reported a delay in medical therapy during COVID-19, but there were no differences in the need for corticosteroids, a change in medical therapy, or IBD-related surgery or hospitalization during or post-COVID-19 compared to the prior 6 months. Microbiome composition stratified by underlying IBD disease activity, but did not show significant change post-COVID-19 (Figure 1). Conclusion: COVID-19 showed no durable impact on clinical IBD disease activity or microbiome composition supporting guidelines for continued maintenance care.